Lessons From the Covid-19 Pandemic: Student Evaluation of a Newly Implemented Flipped Classroom Approach - António Velha1, Noélia Custódio, Maria Carmo-Fonseca, Madalena Patrício (Journal of the Portuguese Society of Anesthesiology, 2024)
Lessons From the Covid-19 Pandemic: Student Evaluation of a Newly Implemented Flipped Classroom Approach